Features of brain activity in alcohol dependence in the task of inhibitory control - S. A. Galkin; A. G. Peshkovskaya; O. V. Roshchina; N. I. Kisel; S. A. Ivanova; N. A. Bokhan (Бюллетень сибирской медицины, 2021)
Objective. To study neurophysiological correlates of inhibitory control to determine the features of inhibitionprocesses in alcohol dependence.Materials and methods. 77 patients with alcohol dependence were examined (42 men and 35 women) (F10.2 according to ICD-10). Patients were examined using a test to assess inhibitory control – Go/No – go. According to the task performance, patients were divided into two groups: group 1 – without inhibitory control impairments, group 2 – with impaired inhibitory control. During execution of test, electroencephalogram recordings were made according to the 10–20 system. The values of spectral power and coherence of θ-, α- and β-rhythms were analyzed. Statistical processing was carried out using nonparametric Mann–Whitney U-test and Wilcoxon W-test.Results. In patients with impaired inhibitory control, there was a decrease in the spectral power of the α-rhythm in the frontal cortex (p = 0.003), whereas in patients without inhibitory control disorders – in the Central cortex (p = 0.036). Patients with impaired inhibitory control responded by increasing β-power to cognitive stimulus in the occipital (p = 0.014), left temporal (p = 0.009) and right temporal (p = 0.008) cortex, while patients without inhibitory control disorders showed an increase in β-power only in the occipital (p = 0.007) and left temporal (p = 0.002) cortex. According to coherence data, patients with impaired inhibitory control have greater involvement of brain structures during the “Go/No – go” test in all frequency ranges.Conclusions. Patients with and without impaired inhibitory control have regional differences in changes in brain bioelectric activity during the “Go/No – go” test.